A new microinvertebrate with features of mites and tardigrades in Dominican amber. Issue 4 (28th September 2019) - Poinar, George; Nelson, Diane R.
Abstract: From time to time, small, fragile, previously unknown fossil invertebrates are found in specialized habitats. Occasionally, as in the present case, a fragment of the original habitat that existed millions of years ago is also preserved. The present article describes a previously unknown microinvertebrate in Dominican amber that cannot be placed in any group of extant invertebrates. Placed in a new family, genus, and species, the fossil shares characters with both tardigrades and mites, but clearly belongs to neither group. The several hundred fossil individuals preserved in the amber shared their moist, warm habitat with pseudoscorpions, nematodes, fungi, and protozoa. The large number of fossils provided additional evidence of their biology, including their reproductive behavior, developmental stages, and food. While there is no extant group that can accommodate these fossils, and we have no knowledge of any extant descendants, this discovery shows that unique lineages of minute invertebrates were surviving in the mid‐Tertiary.